Set2 Is a Nucleosomal Histone H3-Selective Methyltransferase That Mediates Transcriptional Repression - Strahl, Brian D. (American Society for Microbiology, 2002)
Recent studies of histone methylation have yielded fundamental new insights pertaining to the role of this modification in gene activation as well as in gene silencing. While a number of methylation sites are known to occur on histones, only limited information exists regarding the relevant enzymes that mediate these methylation events. We thus sought to identify native histone methyltransferase (HMT) activities from Saccharomyces cerevisiae. Here, we describe the biochemical purification and characterization of Set2, a novel HMT that is site-specific for lysine 36 (Lys36) of the H3 tail. Using an antiserum directed against Lys36 methylation in H3, we show that Set2, via its SET domain, is responsible for methylation at this site in vivo. Tethering of Set2 to a heterologous promoter reveals that Set2 represses transcription, and part of this repression is mediated through the HMT activity of the SET domain. These results suggest that Set2 and methylation at H3 Lys36 play a role in the repression of gene transcription.